The TYPES OF ILLOCUTIONARY ACTS FOUND IN INCREDIBLE 2 MOVIE: A SPEECH ACT ANALYSIS - Kusuma Dewi, Ni Kadek Dita Novia; Putu Devi Maharani; Ida Bagus Gde Nova Winarta (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
This study focuses on the analysis of the illocutionary act in the Incredible 2 movie which contains various kinds of illocutionary acts. In this study, there are 2 problems that will be discussed, namely; What types of illocutionary acts are found in the Incredible 2 movie? and What is the meaning of the illocutionary acts shown in some of the character utterances in the Incredible 2 movie? This study used the theory of Searle (1979) about the types of illocutionary acts and theory of meaning by Leech's (1981) and is supported by the contextual situation theory by Halliday (1985). The data collected from the conversational interactions between characters in the movie Incredible 2 and the analysis used qualitative methods. The method used in presenting the data are formal and informal methods used to analyze 24 data that were found in Incredible 2. The result found expressive illocutionary act is the most commonly occurred with 10 or 41,6% data, and followed by commissive 6 or 25% data, directive 5 or 21% data, representative 2 or 8,3% data and declarative 1 or 4,1% data.